The flood risk management plan: towards spatial water governance. Issue 2 (31st October 2013) - Hartmann, T.; Driessen, P.
Abstract: The flood risk management plan challenges both water engineers and spatial planners. It calls for a new mode of governance for flood risk management. This contribution analyses how this mode of governance distinguishes from prevalent approaches. Spatial planning and water management in Europe are explored in terms of their actor relation, their institutional context, and their approach to the object. These three characteristics of the modes of governance are compared with the governance requirements that flood risk management demands. It is concluded that the governance of flood risk management in Europe should strike a balance between comprehensive and hierarchical planning on the one hand, and interactive planning on the other hand, leading to a spatial water governance.